Unknown Unknowns: Knightian Uncertainty and Corporate Opportunistic Earnings Management - Sabri Boubaker (British Journal of Management, 2023)
Uncertainty is inherent in the real world. Faced with Knightian uncertainty caused by many extreme events, this paper focuses on the analysis of corporate opportunistic earnings management behaviour under the unknown unknowns framework. This paper finds that with an increase in market Knightian uncertainty, corporations will significantly adopt both accrual earnings management and real earnings management. More importantly, when compared with upward earnings management, the results indicate that Knightian uncertainty will lead corporations to implement more downward earnings management. Our results are consistent with the big bath theory, which is also verified through the adjustment of non-recurring profit and loss accounts. To understand the real process of earnings management, we also discuss the strategic choice behaviour of earnings management under different heterogeneous situations.